Konflik Sosial dalam Puisi Mata Luka Sengkon Karta Karya Peri Sandi Huizche dan Relevansinya bagi Pembelajaran Prosa - Puspita, Rossy Widya; Solichin, M. Badrus (MARDIBASA: Jurnal Pembelajaran Bahasa dan Sastra Indonesia, 2024)
This study aims to describe social conflicts in the poem "Mata Luka Sengkon Karta" by Peri Sandi Huizche. The poem narrates the events surrounding the G30S-PKI incident and the aftermath of the ensuing bloodshed, which led to oppression and injustice experienced by the lower-class society, specifically the lives of Bojongsari farmers. These farmers, Sengkon and Karta, were falsely accused of murder and robbery despite being innocent.The research method employed in this study is a qualitative descriptive approach, where the data presented consists of words rather than numbers. The findings of this study reveal the social conflicts depicted in the poem "Mata Luka Sengkon Karta" by Peri Sandi Huizche, which include poverty, political leadership transitions, murder, oppression, and injustice. Additionally, the results of this analysis can serve as teaching material for prose lessons in schools.